Serromyia diabolica, a new biting midge species from Lebanon (Diptera: Ceratopogonidae) - Dominiak, Patrycja; Mathieu, Bruno (Zootaxa, 2015)
A new darkly-pigmented species of Serromyia, closely related to S. subinermis Kieffer, is described from both sexes based on morphological characters and COI gene sequence analyses.